Biogeography and emerging significance of Actinobacteria in Australia and Northern Antarctica soils. (July 2020) - Araujo, Ricardo; Gupta, Vadakattu V.S.R.; Reith, Frank; Bissett, Andrew; Mele, Pauline; Franco, Christopher M.M.
Abstract: Actinobacteria play key roles in terrestrial ecosystem functioning. They contribute to global carbon cycling through the decomposition of soil organic matter, increase plant productivity and are widely known as prolific producers of bioactive compounds essential for human and animal health. The almost century-old search for new members of the Actinobacteria has so far proceeded without systematic investigation of regions where novel, diverse and abundant actinobacterial populations occur. We show that such regions are found in Australia, a dry and warm continent with highly weathered soils. Here, Actinobacteria are highly abundant and evidently well-adapted to the warm, dry soil conditions. Australian continental actinobacterial diversity is associated with physicochemical factors, especially soil pHwater, exchangeable calcium and the regional climate. Patterns of their biogeography suggest that only a small fraction of Actinobacteria have the capability of dispersing throughout the Southern Hemisphere, especially across oceans. We identified a core soil actinobacterial community across mainland Australia of 2211 OTUs which declined to 490 OTUs when Tasmania, King Island, Christmas Island and Northern Antarctica were included. These 490 OTUs mapped to three families, i.e., Gaiellaceae, Micromonosporaceae and Nocardiaceae. Agricultural disturbance reduced actinobacterial diversity, hence undisturbed soils with native vegetation may be reservoirs that enrich the actinobacterial communities in adjacent agricultural soils. Interestingly, high OTU similarities between King Island and areas in Antarctica suggest a shared evolutionary history that persists to this day. In conclusion, the abundance of diverse Actinobacteria taxa in Australian soils suggests an increasingly important function of Actinobacteria as the world's soils become warmer and drier. Graphical abstract: Image 1 Highlights: A continental scale report for Actinobacteria diversity in Australia & N. Antarctica. Actinobacterial diversity is linked to physicochemical factors and regional climate. Agriculture based disturbance reduced actinobacterial diversity. High OTU similarities observed between King Island and areas in Northern Antarctica. Higher abundance and diversity suggest their potential key role in future climates.